Basophil activation test in oral desensitization to cow's milk allergy. Issue 5 (1st October 2016) - Chirumbolo, Salvatore
Abstract : The recent paper by Nucera et al., showed that the basophil activation test (BAT) in flow cytometry is able to monitor an acquired tolerance induced by a desensitization treatment in food allergy. The paper by Nucera et al. reported two standpoints in the CD63 response to food allergy and OAT and their large difference in CD63 response before and after suggests for the optimal performance of a CD123/HLADR/CD63 BAT in oral food allergy immunotherapy.